Sistem Manajemen Keuangan UMKM Rumah Sagu Barokah Dengan Menggunakan Metode Rational Unified Process - Nur Anjeli; Ryci Rahmatil Fiska (Jurnal Publikasi Teknik Informatika, 2025)
UMKM Rumah Sagu Barokah is a small and medium-sized enterprise engaged in the production and sales of sago as its main product. In its daily operations, the financial management system is still carried out manually using handwritten records. This traditional approach has created several problems, such as unorganized and inconsistent documentation of operational expenses including electricity, maintenance, employee salaries, and production costs. As a result, the business owner faces difficulties in controlling expenses, preparing budgets, and evaluating overall financial performance. To address these issues, this study aims to design and implement a Financial Management System based on information technology that can assist UMKM Rumah Sagu Barokah in managing its finances in a more professional, effective, and efficient manner. The system development method employed in this research is the Rational Unified Process (RUP). RUP was chosen because it provides a structured, iterative framework that supports quality improvement through well-defined phases, namely inception, elaboration, construction, and transition. The adoption of this method is expected to enhance project visibility, reduce risks of failure, and ensure the delivery of consistent, high-quality software that meets user requirements. The results of this study demonstrate that the designed financial management system improves efficiency in financial recording, increases data accuracy, and simplifies the preparation of financial reports on a daily, monthly, and annual basis. Moreover, the system provides support for strategic decision-making through more accurate and real-time data analysis. With the implementation of this RUP-based financial management system, UMKM Rumah Sagu Barokah is expected to enhance professionalism in financial management, strengthen its business competitiveness, and support long-term growth and sustainability.